Analysis strategies for longitudinal attachment loss data - James D. Beck and John R. Elter (Blackwell Synergy, 2000)
The purpose of this invited review is to describe and discuss methods currently in use to quantify the progression of attachment loss in epidemiological studies of periodontal disease, and to make recommendations for specific analytic methods based upon the particular design of the study and structure of the data.